Promoting human capital: the importance of dialogic teaching in higher education / Frank Hardman - Hardman, Frank (ACRULeT, Faculty of Education & UiTM Press, 2008)
Over the last 30 years, university education has undergone major changes due to the growing numbers of home and international students, the introduction of information and communication technology and an increasingly managerial approach that evaluates education in terms of cost, efficiency and measurable outcomes. In the face of these changes, universities are charged with the responsibility of providing students with a rich learning environment in which they are taught to reason and think critically, and to develop a range of attributes needed by employers such as team working and enterprise so they can fully participate in the workplace. In addressing these challenges, this paper explores current approaches to learning and teaching in higher education and the role that a dialogic pedagogy can play in shaping thinking and to secure engagement, learning and understanding in university study. It concludes by arguing for more powerful professional development programmes in higher education so as to enhance the pedagogic knowledge of the university teaching community in order to promote higher levels of joint lecturer-student activity in both face-to-face and online interactions.